PREVALENCE OF CRYPTOSPORIDIUM OOCYSTS IN BOVINE AT DIFFERENT LIVESTOCK FARMS BY CONVENTIONAL MICROSCOPIC AND MOLECULAR TECHNIQUES - S. Masood; A. Maqbool; A. A. Anjum; M. I. Rashid; Z. I. Choudhary (Journal of Animal and Plant Sciences, 2013)
Aim of the study was to analyze the prevalence of Cryptosporidiosis in cattle and buffaloes by oocyst microscopic examination and polymerase chain reaction (PCR). Cryptosporidiosis as detected by microscopic examinations was higher in cattle (10.5%) than buffaloes (8.47%) in Lahore from August, 2007-July, 2008. Percent prevalence of cryptosporidiosis in cattle and buffaloes was higher at Governmental dairy farms (20.55 & 16. 66) followed by Gawala colonies (12.77 &9.44), Military dairy farm (6.11 & 4.44) and House hold dairies (3.88 & 3.34). The highest percent prevalence recorded in cattle and buffaloes was during summer (15 & 12), followed by autumn (10.88 & 20), spring (10.88 & 7.5) and the lowest in winter season (6.6 & 4.5). Infection rate was higher in young cattle and buffaloes than older. Non-significant difference was recorded in relation to sex of animals and infection rate. Percent prevalence in cattle (12.22%), as detected by PCR was highest at Governmental dairy farm (22.7%), followed by Gawala colonies(14.41%), Military dairy farm (7.7%) and House hold dairies (5%). Although, the prevalence of Cryptosporidiosis detected by PCR was higher as compared to microscopic examinations, no statistically significant difference was observed. It is concluded that cryptosporidiosis is highly prevalent in Lahore, which insinuates authorities for its monitoring by microscopic or molecular methodsto achieve the production to its maximum potential.
Keywords: Prevalence; Cryptosporidiosis; PCR; age; sex and season